Wir sind nicht auf der Welt, um zu schweigen Eine Einleitung in die Rhetorik - Kopperschmidt, Josef (De Gruyter, 2018)
We are not in the world to mention is the title of a somewhat unconventional "introduction to rhetoric". It is not an introduction to its history or system, but exposes the specific question interest of rhetoric. Since antiquity, rhetoric has been asking for the conditions of convinced approval as the basis for survival cooperation. The notorious conflict of rhetoric with philosophy resulted from the different functionalization of this consent: Should it merely be condoned as a concession to the intellectual weakness of people in order to win them for the acceptance of truth claims (Plato), or must one in the convinced consent requirement rather see the actual reason for possible truthfulness (so the sophistry)? This conflict was only decided after Hans Blumenberg, when direct paths to the truth could no longer be philosophically promised seriously. As a result, the rhetorical principle of convinced approval could finally become philosophically an attractive validity principle under conditions of modernity. Therefore, if today something rhetoric makes current, then it is the modernity of this conviction or consent-dependent validity principle.